Symptoms of Persistent Behavior Problems in Children With Mild Traumatic Brain Injury. Issue 5 (September 2015) - Taylor, H. Gerry; Orchinik, Leah J.; Minich, Nori; Dietrich, Ann; Nuss, Kathryn; Wright, Martha; Bangert, Barbara; Rusin, Jerome; Yeates, Keith Owen; Caplan, Bruce; Bogner, Jennifer; Brenner, Lisa
<x xml:space="preserve">Abstract</x> Objective: To investigate the effects of mild traumatic brain injury (mTBI) in children on symptom ratings of behavior problems across the first-year postinjury. Setting: Emergency departments of 2 regional children's hospitals. Participants: Parents of 176 children with mTBI and 90 children with orthopedic injury aged 8 to 15 years. Design: Group comparisons of postinjury parent and teacher ratings of child behavior problems controlling for background factors. Main Measures: Child Behavior Checklist and Teacher's Report Form. Results: For younger but not older children in the sample, children with mTBI compared with children with orthopedic injury had higher postinjury ratings on the Child Behavior Checklist Total Behavior Problem scale (t264 = 3.34, P < .001) and higher rates of T-scores of 60 or more on this scale (odds ratio = 3.00; 95% confidence interval, 1.33-6.77; P = .008). For children with mTBI, hospitalization, motor vehicle accidents, loss of consciousness, and magnetic resonance imaging abnormality were associated with higher parent or teacher ratings. Conclusions: School-aged children with mTBI are at risk for persistent symptoms of behavior problems, especially if mTBI is more severe or occurs at a younger age. The findings justify monitoring of behavior long after injury and further research to identify risk factors for these symptoms and their association with clinical disorders.